Penerapan Metode G-MAUT Dalam Pemilihan Editor Video Terbaik - Putra, Ade Dwi; An’ars, M. Ghufroni (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
A video editor is a professional who is responsible for processing raw footage into videos that are interesting, structured, and in accordance with the project's objectives. Choosing the best video editor requires careful consideration to evaluate their mastery of popular editing software, as well as additional capabilities such as color correction, audio processing, and visual effects. The main problem in choosing the best video editor often has to do with the difficulty of objectively assessing quality and ability before working together. Problems in the best video editor rating often arise due to the subjective nature of the work and depend on aesthetic preferences as well as the specific needs of the project. This study aims to apply the G-MAUT method in the process of selecting the best video editor. The main goal is to produce an objective, systematic, and multi-criteria-based assessment system to help make more accurate decisions. By using the G-MAUT method, this research can provide solutions that can improve efficiency and fairness in the election process, as well as contribute to the development of decision support systems in the creative field. The results of the calculation using the G-MAUT method in the ranking of the best video editor selection were obtained by Candidate C managed to rank first with the highest final score, which was 0.7794, showing superior performance compared to other candidates. In second place, there is Candidate A with a score of 0.4241, which still shows a significant contribution even though it is quite far from the first place. Candidate D followed in third place with a score of 0.3573. These results illustrate the stark differences among the candidates, providing important insights for further evaluation.